Review Penggunaan Reduced Graphene Oxide/TiO2 sebagai Fotoelektrode pada Dye-Sensitized Solar Cell - Eka Cahya Prima; Meilisyah Putri Utami; Andhy Setiawan; Endi Suhendi (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2022)
Many studies on graphene applied to DSSC have been carried out with the aim of increasing the efficiency of power conversion in organic solar cells. This research was conducted to find the best composition of soar cells so that they can be utilized and converted into electrical energy. The use of graphene as a photoanode can increase the conversion efficiency along with good electrical conductivity values in graphene. This review aims to analyze the process of increasing power conversion efficiency in DSSC caused by the addition of graphene to TiO2 which acts as a photoanode in DSSC during the last five years. The results of the measurement of DSSC efficiency increased when the addition of reduced graphene oxide to TiO2 was carried out.